Professional in prenatal care for homeless pregnant women: integrative review (Research, Society and Development, 2020)
Objective: to discuss the performance of the multidisciplinary prenatal team for homeless pregnant women. Method: integrative review conducted at the Pubmed / Medline Portal, VHL Regional / Lilacs and the EMBASE, SCOPUS and CINAHL databases. Guiding question followed the PICo strategy: How does the multidisciplinary team act in prenatal care for pregnant women on the street? Inclusion criteria: full texts of the health areas related to the prenatal professional performance of pregnant women on the street, in the period 2009 and 2018. Exclusion criteria: gray literature, duplicate articles and those that do not include the studied theme. Results: The activities of professionals in the prenatal care of pregnant women on the street are like those recommended for all pregnant women, with the addition of referrals and specific activities for the prevention of drug use and sexually transmitted infections. Studies have revealed that structural, logistical, and attitudinal obstacles have negatively influenced the adherence of pregnant women. Conclusion: The multi-professional team in the prenatal care of pregnant women on the street develops the same activities with other pregnant women, with an emphasis on preventing drug use and sexually transmitted infections.